DIALECTICAL BEHAVIOUR THERAPY: OVERVIEW OF A PROPOSAL CENTERED ON UNCONDITIONAL ACCEPTANCE - Ramírez Henderson, Ronald (2013)
This article reviews the Dialectical Behaviour Therapy (DBT), which is a psychological intervention model based on unconditional acceptance of the person’s behaviour in conjunction with promoting behavioural changes through the dialectical interaction between both tendencies. The article states the emergence of the model, its foundations, its main strategies, its modes of intervention and its phases of the treatment. It concludes with a consideration about the implications of adapting the model in Costa Rica.